Factors Affecting the Performance and Applicability of SrTiO3 Photoelectrodes for Photoinduced Cathodic Protection - Yang, Yao; Cheng, Y. Frank (Journal of the Electrochemical Society, 2017)
In this work, various factors affecting the applicability and performance of prepared SrTiO3 photoelectrodes for photoinduced cathodic protection (CP) were investigated. The capability of the photoelectrode for photoinduced CP depends on the type of steels to be protected. A higher photo current density is required to cathodically protect X52 carbon steel than 304 stainless steel. Threshold areas of the photoelectrode relative to that of the cathode exist for both steels to enable photoinduced CP. The threshold area ratio of the SrTiO3 photoelectrode to X52 carbon steel is 8: 1 in 3.5 wt% NaCl solution, while, for 304 stainless steel, the area ratio of 1: 1 is sufficient for photoinduced CP. The photoinduced CP performance depends on the hole scavenger used in the photoelectrode cell. Na2S is an effective hole scavenger, and both X52 carbon and 304 stainless steels are cathodically polarized by photoelectrons to sufficiently negative values for a full CP. Moreover, the SrTiO3 photoelectrode can fully protect X52 steel only when the light intensity is up to 125 mW/cm2, while a light intensity of 50 mW/cm2 enables a full CP on 304 stainless steel. The photoinduced CP performance is also subject to the corrosivity of the solutions.